Analysis Of Ecoprint Results On Cotton Material Using Kenikir Leaves (Cosmos Caudatus) With Mordant Mixture - Diva, Rahmatul; Novrita, I Sri Zulfia (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2023)
This research was motivated by the effect of mordant mixture on the results of kenikir leaf  ecoprint.  The  purpose  of  this  study  is  to  describe  the  direction  of  color  names, clarity of motifs and the effect of mordant mixtures on ecoprint results. This research is  experimental  descriptive  quantitative  research  conducted  by  making  an  ecoprint with steam blanket technique with the combination of 3 mordants. The mordants used were alum, arbor, soda abu, sodium acetate and whiting. The natural motif used was kenikir  leaves  (cosmos  caudatus).  The  dye  used  is  secang.  The  type  of  data  in  this study  is  primary  data  with  data  collection  techniques  in  the  form  of  questionnaires. The data analysis technique uses frequency percentages and uses the SPSS (Statistical Product And Service Solution) Version 27.0 program. The color name direction of the leaves  using  a  mixture  of  alum,  arbor,  and  soda  abu  produces  an  olive  color.  A mixture  of  alum,  arbor,  and  sodium  acetate  produces  a  dark  brown  color.  The mixture of alum, arbor, and whiting produces a dark Olive Green color.  The results of  the  motif  clarity  test  with  a  mixture  of  alum,  arbor,  soda  abu  are  categorized  as clear, a mixture of alum, arbor, sodium acetate is categorized as clear while a mixture of alum, arbor, and whiting is categorized as unclear.